INCREASING STUDENTS’ VOCABULARY THROUG ENGAGE STUDY AND ACTIVE METHOD AT THE SECOND GRADE OF SMP 3 LEMBANG PINRANG REGENCY - Daharia A. (ETERNAL (English, Teaching, Learning and Research Journal), 2016)
The objective of this research is to know whether the ESA method can increase the student vocabulary mastery at the second grade of SMP 3 Lembang Pinrang Regency. This study was focused on increasing students’ vocabulary mastery through ESA method. The method of this research was classroom action research. It was conducted in two cycles. Each cycle consisted of four meetings. The data analysis techniques used qualitative and quantitative technique. The technique of data collected was observation, interview and test.It was found that the student achievement and the performance from the first to the second cycle increased where in the first cycle the students’ mean score only 64 percent which classified as “fair Good score” while in the second cycle the students’ mean score is 82 percent which classified as “Good score”. It can be said that, this research is successful because the students’ score has achieved the research target. It is 75 percent as score of KKM in SMP 3 Lembang Pinrang Regency. In conclusion ESA method can increase the students’ vocabulary mastery.